Efficiency of trickle irrigation and antitranspirants on nutrient availability and fruit production of Kinnow mandarin (Citrus reticulata Blanco) under rainfed condition - KUMAR, VIJAY; SINGH, PERMENDRA; KUMAR, MANOJ; KOTWAL, NEERAJ; KUMAR, SANJEEV (Journal of Soil and Water Conservation, 2025)
A field experiment was conducted during 2019 and 2020 at research farm of RRSS- SKUAST-Jammu to study the change of nutrient status and fruit production Kinnow mandarin through trickle irrigation and antitranspirants under rainfed conditions. The study was carried out in randomized block design in which fifteen treatments and replicated thrice. The two years pooled data was revealed that the maximum was obtained three days trickle irrigation intervals with foliar spray of kaolin (4%) of total chlorophyll (44.71), total water content (58.48 %), leaf water deficit (25.10 %), and leaf areas (45.24 cm) respectively. The range from organic carbon (4.43-4.54 g kg-1), available nutrients like nitrogen (209.27- 214.89 kg ha- 1), phosphorus (14.19-16.27 kg ha-1) and potassium (145.18- 157.31 kg ha-1) respectively were achieved. The leaf nutrient (N, P K, Ca and Mg) analysis exposed that three days trickle irrigation intervals with foliar spray of magnesium carbonate (4%) formed significantly (p